UUD 1945, P4, GBHN ( TAP MPR No. II/MPR/1988 ), TAP-TAP MPR 1988, Pidato pertanggungjawaban Presiden/Mandataris MPR : bahan penataran dan bahan referensi penataran - Indonesia (Depdikbud, 1988)
xvi, 707 p.; 15 cm.